Pengolahan Air Tanah Dalam Menurunkan Bakteri Coliform Dengan Metode Mikrofiltrasi Dengan Media Membran Keramik - Fawaz, Hammam; Firra Rosariawari; Praditya S. Ardisty Sitogasa (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Groundwater treatment to reduce Coliform Bacteria levels generally still uses chlorine chemicals. Although effective, on the other hand, chlorine chemicals cause another problem, namely residual chlorine which is harmful to health if the treated water is used directly. Therefore, ceramic membranes can be used as an alternative to degrade Coliform Bacteria levels without causing side effects. The materials used as components of the ceramic membrane are clay, zeolite and coconut shell charcoal, with 3 groups of composition comparisons and 2 types of thickness. This research is experimental by carrying out a simple filtration process using a tube continuously, within an operating period of 8 hours. This study aims to analyze the effect of variations in the composition and thickness of the ceramic membrane on its performance used as filtration. The results of the filtration process show that the variation in the composition of the membrane 50%:25%:25% with a thickness of 2.5 cm has the highest reduction efficiency reaching 95.88%. This ceramic membrane variation has the least mixture of coconut charcoal. The study revealed that the mixture of additives in the form of coconut charcoal and membrane thickness play an important role in pore formation. The more clay and coconut shell charcoal are mixed and the thicker the membrane is made, the more the ceramic membrane's ability to reduce water pollutant levels will increase.